How does Spiritual Leadership Influences Employee Well-Being? Findings from PLS-SEM and FsQCA - Chwen-Li Chang; Ivon Arisanti (Ital Publication, 2022)
This study aims to examine the relationship between spiritual leadership, affective commitment, work engagement, and employee well-being. In this test, the hypotheses of 356 public sector employees through Partial Least Squares-Structural Equation Modeling (PLS-SEM) and fuzzy set Qualitative Comparative Analysis (fsQCA). PLS-SEM results show that spiritual leadership affects affective commitment, work engagement, and employee well-being and shows that affective commitment and work engagement have different effects because of parallel mediation with spiritual leadership in improving employee well-being. The results of the FsQCA provide theoretical insights and practical recommendations on how to improve understanding of spiritual leadership, affective commitment, work engagement, and employee well-being. This research has implications for policymakers, especially in the public sector, to support and develop spiritual practices that can help employees improve employee well-being through affective commitment and work engagement. In addition, this research can help organizations improve the performance of individuals in organizations, especially public organizations, to make positive contributions to society at large. Doi: 10.28991/ESJ-2022-06-06-09 Full Text: PDF